Measurement of the Cut Off Score of Visual Function Questionnaire on Vision Related Quality of Life to Predict Severity of Diabetic Retinopathy - Fauziah Hayati; Arief Kartasasmita; Mayang Rini; Feti Karfiati (Majalah Oftalmologi Indonesia, 2015)
Background: Diabetic retinopathy has a negative impact on quality of life. In order to investigate the effects of visual impairment in self-perception of quality of life, vision related questionnaires such as the National Institute Visual Function Questionnaire (NEI-VFQ-25) has been developed. The aim of this study is to predict severity of diabetic retinopathy using NEI-VFQ-25 Version 2000 by measuring the cut off score of visual function questionnaire on vision related quality of life Methods: Cross Sectional study by examining 49 diabetic retinopathy patients who meet the inclusion criteria. All patients requested to answer the questionnaire. All question have a score and all question scores then categorized into a number of subscales that can be averaged to yield the subscale scores (lowest to highest range 0-100). Higher score on the VFQâ€“25 indicates better visual function and health related quality of life. Average scoring then being analyzed by ROC curve in order to gain the cut off score value between retinopathy and sight threatening diabetic retinopathy. Results: The cut off score value between retinopathy and sight threatening diabetic retinopathy is 90.90. The VFQ-25 classification score is in the range of <90.90 consider threatening diabetic retinopathy and â‰¥90.90 consider retinopathy. Conclusion: VFQ-25 is one of the instruments to confirm that diabetic retinopathy significantly impair quality of life. The cut off score value between retinopathy and sight threatening diabetic retinopathy is 90.90. Keywords: Diabetic retinopathy, NEI-VFQ-25